2020
DOI: 10.3390/molecules25235649
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Biomaterials for Drug Delivery

Abstract: The development of precise and personalized medicine requires novel formulation strategies to deliver the therapeutic payloads to the pathological tissues, producing enhanced therapeutic outcome and reduced side effects. As many diseased tissues are feathered with acidic characteristics microenvironment, pH-sensitive biomaterials for drug delivery present great promise for the purpose, which could protect the therapeutic payloads from metabolism and degradation during in vivo circulation and exhibit responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(89 citation statements)
references
References 188 publications
(197 reference statements)
0
79
0
Order By: Relevance
“…These are most commonly used for triggering the release of the drug among the other stimuli. The traditionally used pH-responsive carriers show their effects based on the pH of different organs such as the intestine and stomach [ 142 ]. pH-responsive polymers can be either polyacids (which sense and release at basic pH) or polybases (which sense acidic pH and release the drug).…”
Section: Stimuli-responsive Drug Delivery Systems Using Smart Biomaterialsmentioning
confidence: 99%
“…These are most commonly used for triggering the release of the drug among the other stimuli. The traditionally used pH-responsive carriers show their effects based on the pH of different organs such as the intestine and stomach [ 142 ]. pH-responsive polymers can be either polyacids (which sense and release at basic pH) or polybases (which sense acidic pH and release the drug).…”
Section: Stimuli-responsive Drug Delivery Systems Using Smart Biomaterialsmentioning
confidence: 99%
“…In a weakly acidic environment, the ester bond or amide bond can be hydrolyzed to release the connected drug. 53–55 In our study, PTX was coupled with PEG by the pH-sensitive β-carboxylic amide linkage, which could improve the hydrophilicity of PTX and could be further self-assembled to nanoparticles. Similarly, PT with metallic properties linked with LA increased load efficiency in NPs.…”
Section: Discussionmentioning
confidence: 92%
“…Further experiments showed that the ACPP-DOX cellular uptake was improved after enzymatic-triggered activation, and ACPP-DOX efficiently repressed HT-1080 cell proliferation [ 165 ]. As several tumor tissues are characterized with an acidic microenvironment, drug delivery via pH-sensitive biomaterials display significant potential for responsive release of therapeutics triggered via acidic pathological tissues in tumor sites [ 166 ] ( Figure 8 ). In a related study, the ACCP CR 8 G 3 PK 6 , with a shielding group of 2,3- dimethylmaleic anhydride (DMA), was conjugated to DOX to build a novel prodrug named DOX-ACPP-DMA for tumor-targeted drug delivery [ 167 ].…”
Section: Delivery Of Chemotherapeuticsmentioning
confidence: 99%